2013
DOI: 10.1093/mnrasl/slt117
|View full text |Cite
|
Sign up to set email alerts
|

A synchrotron jet from a post-asymptotic giant branch star

Abstract: The evolution of low-and intermediate-initial-mass stars beyond the asymptotic giant branch (AGB) remains poorly understood. High-velocity outflows launched shortly after the AGB phase are thought to be the primary shaping mechanism of bipolar and multipolar planetary nebulae (PNe). However, little is known about the launching and driving mechanism for these jets, whose momentum and energy often far exceed the energy that can be provided by radiation pressure alone. Here, we report direct evidence of a magneti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 27 publications
4
27
0
Order By: Relevance
“…Among them, the SED measured towards WF IRAS 15445−5449 was found to display a steep negative spectral index between ≈ 5 GHz and ≈ 8.7 GHz. Pérez-Sánchez et al (2013) confirmed that the non-thermal emission is arising from a synchrotron jet, spatially resolved at 22 GHz.…”
Section: Radio Continuum and The Spectral Energy Distributionsupporting
confidence: 54%
See 2 more Smart Citations
“…Among them, the SED measured towards WF IRAS 15445−5449 was found to display a steep negative spectral index between ≈ 5 GHz and ≈ 8.7 GHz. Pérez-Sánchez et al (2013) confirmed that the non-thermal emission is arising from a synchrotron jet, spatially resolved at 22 GHz.…”
Section: Radio Continuum and The Spectral Energy Distributionsupporting
confidence: 54%
“…This scenario implies the presence of a strong magnetic field which could be related to the collimation of the high-velocity outflow traced by the H 2 O maser emission (e.g. Pérez-Sánchez et al 2013). Nonetheless, new observations of radio continuum emission above 10 GHz are needed in order to probe the source of the non-thermal component.…”
Section: Radio Continuum Flux: Radio Jet or Hii Region?mentioning
confidence: 99%
See 1 more Smart Citation
“…Many new observations and theoretical studies since the turn of the Millennium further consolidated the jet-shaping scenario of many PNe (e.g., Parthasarathy et al 2000;Bujarrabal et al 2001;Miranda et al 2001;Corradi et al 2001b;Guerrero et al 2001;Imai et al 2002;Riera et al 2003;Vinković et al 2004;Huggins et al 2004;Peña et al 2004;Balick & Hajian 2004;Arrieta et al 2005;Oppenheimer et al 2005;Sahai et al 2005;Vlemmings et al 2006;Miranda et al 2010;Nakashima et al 2010;Phillips et al 2010;Sahai et al 2011;Szyszka et al 2011;López et al 2012;Clark et al 2013;Pérez-Sánchez et al 2013;Vlemmings et al 2014;Fang et al 2015 Dennis et al 2008Dennis et al , 2009Lee et al 2009;Huarte-Espinosa et al 2012;Velázquez et al 2012;Balick et al 2013;Velázquez et al 2014 for theoretical studies; these papers composed a small fraction of the papers studying jets in PNe). X-ray observations seem also to support the presence of jet-inflated bubbles and of jets Sahai et al 2003), similar to X-ray jets in symbiotic systems (e.g., Kellogg et al 2001;Galloway & Sokoloski 2004).…”
Section: Pn Morphologiesmentioning
confidence: 99%
“…Decin et al 2012), magnetic fields (e.g. Pérez-Sánchez et al 2013;van Marle et al 2014), or binarity (Soker 1997;Huggins 2007). The latter need not be surprising as the multiplicity frequency of the progenitors of AGB stars is above 50 percent Article published by EDP Sciences A118, page 1 of 26 (Raghavan et al 2010;Duchêne et al 2013).…”
Section: Introductionmentioning
confidence: 99%